ANALISIS PENYEBAB KERUSAKAN JALAN PADA TANAH EKSPANSIF DAN ALTERNATIF PENANGANANNYA (Studi Kasus Jalan Padangan â Batas Ngawi) - , Intan Yuniarti ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Road damage occurs continuously on the road from Padangan â Boundary of Ngawi has not found its possible causes to determine the right treatment. The possible cause of the damage was allegedly caused by expansive soil conditions. Sub grade has an important role to the pavement structure on it. This research was intended to analyze the damage to the flexible pavement from km 03+000 to Km 30+500 related to pavement thickness and subgrade conditions, to analyze the influence of expansive pressure and potential of sub grade soil, and recommend treatment alternative of road damage in accordance with its types and causes of damage. The analysis were based on data from Ditjen Bina Marga Surabaya and the result of direct survey on the field. The research consist of sampling the soil, laboratory testing, and soil classification was determined using Unified system and AASHTO. The analysis of swelling potential used measurement method (indirect method) by Seed (1962) and classification method (indirect method) by Chen (1975), while to analyze the pavement thickness was designed using AASHTO (1993). The research result shows that the the existing condition has thirteen locations with severely damage, with types of damage such as longitudinal cracking, edge cracking, block cracking, upheaval, depression, potholes, and swelling. Based on AASHTO and laboratory testing, main factor that causing road damage is pavement structure does not eligible the requirement of thickness, and expansive degree of its subgrade is critical and very high swelling pressure. Recommended treatment of its road damage such as pavement nor subgrade rehabilitation, appropriate with type and level of the damage. Pavement rehabilitation according to AASHTO must be first to do subgrade rehabilitation, for instance treatment by using geomembrane. Drainage improvement also should be done. AASHTO analysis advises overlay thickness is 15 centimetre. The alternative if without overlay is structural treatment using Cakar Ayam system for very high shrink - swell area.